Effect of Fertigation Levels on Water Consumption, Soil Total Nitrogen, and Growth Parameters of Brassica Chinensis under Straw Burial. Issue 1 (2nd January 2021) - Rasool, Ghulam; Xiangping, Guo; Zhenchang, Wang; Sheng, Chen; Ullah, Ikram; Ali, Muhammad Usman; Saifullah, Muhammad
ABSTRACT: The inefficiency and excessiveness of nitrogen fertilizer usage is an alarming concern in China with adverse effects on economy and environment. The experiments were conducted to study the effect of straw burial coupled with fertigation levels on the water consumption, soil total nitrogen, and growth of Brassica Chinensis. A complete randomized factorial design was established comprising straw burial, nitrogen fertilizer, and irrigation water, each with two levels. The treatments were established as; T1 :S-F2 I1, T2 :S+ F2 I1, T3 :S-F2 I2, T4 :S+ F2 I2, T5 :S-F1 I1, T6 :S+ F1 I1, T7 :S-F1 I2, and T8 :S+ F1 I2, where, S-: No straw burial, S+ : with straw burial, F1 : 120 kg ha −1, F2 : 80 kg ha −1 of nitrogen fertilizer. The results revealed that straw burial saved 7.34 and 9.50% more irrigation water in SS and WS, respectively, when compared with no straw treatments. When compared with T5 (S-F1 I1 ), all other treatments decreased soil TN of D10 and D30 soil layers during both seasons, whereas the highest increase in soil TN of D20 soil layer was observed under straw burial. Comparing with T5, the highest decrease in leaf number and leaf area index was found in T3 (35.78 and 66.27% respectively). Comparing with T5, the highest increase in shoot and roots dry biomass was found under T4 (16.95% and 6.14% respectively). Comparing with T5, the lowest and highest decrease in the fresh yield of Brassica Chinensis was found under T4 (15.83%) and T3 (41.63%) respectively. Comparing with T5, the highest increase in WUEs and PFPs of Brassica Chinensis was also found under T4 . It is therefore concluded that straw burial can store total nitrogen in the upper rootzone and can also alleviate the negative effect of nitrogen and irrigation water under limited conditions.